A constraint-led approach to sport and physical education pedagogy - Renshaw, Ian; Chow, J-Y (Physical education and sport pedagogy, 2019)
The Constraints-Led Approach (CLA) has emerged as a viable pedagogical option for teachers and coaches in the sport and physical education. The emergence of a CLA to teaching and coaching has paralleled a change in the current zeitgeist with many scientists embracing the ideas of complexity and a more ecologically driven agenda. The CLA articulates that through the interaction of different constraints - task, environment, and performer - a learner will self-organise in attempts to generate effective movement solutions [Renshaw, Ian, Keith Davids, Elissa Phillips, and Hugo Kerherve. 2011. "Developing Talent in Athletes as Complex Neurobiological Systems." In Talent Identification and Development in Sport: International Perspectives, edited by Joe Baker, Stephen Cobley, and Jorg Schorer. London: Routledge]. However, successful employment of a CLA requires an understanding of ecological dynamics as these underpinning concepts manifest themselves as guiding principles for the design of CLA practice environments. While some practitioners are adopting the ideas of CLA in their work, there is some concern that the often dense academic language often associated with the approach is acting as a key barrier in the take up of CLA and resulting in a limited understanding of the key underpinning concepts and hence poor implementation. It is therefore incumbent on advocates of CLA to provide pedagogues with the knowledge and tools to base learning design on the key principles of CLA. In this paper, we walk the reader through the key theoretical concepts in CLA. We introduce the key ideas underpinning a CLA to provide guidelines as to how practitioners can implement a CLA in their practice. Wherever possible, we provide 'exemplars' from sport and pedagogy settings in an attempt to de-mystify the potentially confronting language of the ecological dynamics landscape. We make clear that simply adopting a CLA should not be seen as a panacea for practitioners and conclude by emphasising that effective CLA teaching and coaching practice is therefore subject to the same pedagogical requirements when designing learning activities as when providing more traditional approaches.